Paula Deen ventures : business partnerships imperiled over a choice of words (A) - Brinkley, Choni; Kellner, Jennifer; Zicarelli, Jackie Tomaszewski; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
In 2012, a former employee filed a lawsuit against Deen and her brother for racial discrimination. Deen later confessed to using racial slurs in a deposition transcript that was leaked in 2013. Deen issued a public apology. But several companies, including the Food Network, elected to end their partnership with Deen. Can Paula Deen recover?
Originally published in Brinkley, C., Kellner, J., Tomaszewski Zicarelli, J., & ORourke, J. S. (2015). Paula Deen Ventures: Business partnerships imperiled over a choice of words (A). 15-04 (A). Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Deen, Paula H., -- 1947-; Food Network (Firm); Strategic alliances (Business); Partnership